A new strategy to recover from volatile fatty acid inhibition in anaerobic digestion by photosynthetic bacteria. (September 2020) - Zhao, Weixin; Jeanne Huang, Jinhui; Hua, Binbin; Huang, Zhiyong; Droste, Ronald L.; Chen, Lu; Wang, Bo; Yang, Chen; Yang, Shasha
Graphical abstract: Highlights: PSB could release VFAs inhibition and recover biogas production effectively. PSB bioaugmentation could maintain the microbial diversity of the system. Light could accelerate the consuming speed of VFAs with or without PSB addition. Adding PSB to release VFAs inhibition might be a cost-effective choice. Abstract: The accumulation of volatile fatty acids (VFAs) can decrease reactor pH and inhibit methane-producing process. For the first time, photosynthetic bacteria (PSB) were used to recover from VFAs inhibition (pH 6.0) of an anaerobic digestion system. After adding PSB for 12 days with and without light condition, the methane content recovered from 33.3% to 60.5% and from 32.1% to 59.3%, respectively; the pH increased to 7.1 and 6.8, respectively, the system alkalinity rapidly increased to 2238 and 1921 mg/L, respectively; the sCOD decreased from 5600 to 995 mg/L and from 5575 to 2025 mg/L, respectively; and the contents of formic acid, acetic acid, propionic acid and total VFA were greatly reduced. Microbial analysis found that PSB bioaugmentation could maintain microbial diversity of the system. PSB bioaugmentation could effectively relieve acids accumulation and stimulate methane production especially under light condition. It is also found that light could accelerate recovery with or without bioaugmentation.